The usage behavior of the Malaysian business reporting system among financial reporting preparers in Malaysia. - Roslee, Uyob (2024)
The Malaysian Business Reporting System (MBRS) is an online submission platform that employs the Extensible Business Reporting Language (XBRL) format to enhance efficiency and address challenges posed by traditional paper-based systems. Despite its advantages, MBRS has experienced slow adoption, with only three point seven percent of financial reporting submissions utilizing the platform within a year of its introduction. This study aims to investigate the current state of MBRS utilization and comprehensively understand the factors influencing Malaysian financial reporting preparers' behaviour toward adopting MBRS. Employing a quantitative research approach, 267 members of the Malaysian Institute of Accountants (MIA) who engaged in financial report preparation and submission to the Suruhanjaya Syarikat Malaysia (SSM) participated in this study. Data was collected using self-administered survey questionnaires and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The study found that while MBRS usage rates are still low, 83.1 % of financial reporting preparers display a keen interest in participating in MBRS training sessions again. In terms of influential factors, the study identifies that the intention to use MBRS significantly shapes MBRS usage behaviour. Preparers' satisfaction, perceived usefulness and perceived ease of use emerged as significant determinants of the intention. However, elements of attitude, perceived compatibility and perceived cost, do not exert the same level of impact. Moreover, the study underscores the role of perceived incentives in reinforcing the link between intention and actual MBRS usage behaviour. The findings of this study hold the potential to guide pertinent regulatory bodies, particularly SSM, in optimizing the adoption behaviour of MBRS among financial reporting preparers.